National recovery strategy for woodland caribou (Rangifer tarandus caribou), boreal population, in Canada - Dave Hervieux (Rangifer, 2007)
Recovery planning for the boreal population of woodland caribou is a complex task, spanning eight Canadian provinces and territories. To accommodate unique situations across the country, recovery planning for this Species at Risk Act-listed threatened species is occurring at both provincial/ territorial and national levels. The national recovery strategy strives to identify nationally important issues and provide direction for provinces and territories as they plan and implement boreal caribou recovery within their jurisdictions. The national vision is to conserve and recover boreal caribou and their habitat across Canada. Specific goals are to: 1) Prevent extirpation of local boreal caribou populations from all existing caribou ranges; and 2) Maintain or enhance local boreal caribou populations at or to self-sustaining levels within all existing caribou ranges; and 3) Maintain or enhance boreal caribou habitat to support self-sustaining local populations. Nineteen broad national approaches are identified. These approaches include items relating to: habitat planning and management, caribou population monitoring and management, management of human-caused mortality, management of other wildlife species, consideration of government legislation and policy,promotion of stewardship and public outreach, and research. Specific outcomes are provided for each stated recovery approach. For more information on Canada's national recovery strategy for the boreal population of woodland caribou please see www.speciesatrisk.gc.ca/recovery/default_e.cfm